TO THE QUESTION ABOUT CONNECTION OF ORE FORMATION WITH GEOCHEMICAL EVOLUTION OF SOME GRANITOIDS OF THE NORTH-WESTERN REGION OF THE UKRAINIAN SHIELD - MIKHILICHENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The potential ore resources of the granitoids of the charnockite-granite stage of the North-Western region of the Ukrainian Shield are analysed on basis criterions of whole-rock major element geochemistry. The connection of ore formation with geochemical evolution of the granitoids is shown.